Energetic Particle Precipitation: A Major Driver of the Ozone Budget in the Antarctic Upper Stratosphere - Cordero-Carrasco, R (Blackwell Publishing Ltd, 2016)
Geomagnetic activity is thought to affect ozone and, possibly, climate in polar regions via energetic particle precipitation (EPP) but observational evidence of its importance in the seasonal stratospheric ozone variation on long time scales is still lacking. Here we fill this gap by showing that at high southern latitudes, late winter ozone series, covering the 1979-2014 period, exhibit an average stratospheric depletion of about 10-15% on a monthly basis caused by EPP. Daily observations indicate that every austral winter EPP-induced low ozone concentrations appear at about 45 km in late June and descend later to 30 km, before disappearing by September. Such stratospheric variations are coupled with mesospheric ozone changes also driven by EPP. No significant correlation between these ozone variations and solar ultraviolet irradiance has been found. This suggests the need of including the EPP forcing in both ozone model simulations and trend analysis. © 2016. American Geophysical Union. All Rights Reserved.